Diagnosis of Leptospirosis in Animals and Human by Dark Field Microscopy and Polymerase Chain Reaction - Bojiraj, M.; Porteen, K.; Gunaseelan, L.; Kannan, S. Suresh (International Journal of Livestock Research, 2018)
Leptospirosis is an economically important disease affecting the most of domestic animals. A study was conducted to investigate the prevalence of leptospirosis in animals and human by Dark field microscopy and Polymerase chain reaction targeting the Lip L32 gene. A total of 775 samples comprising of 118 canine (108 sera and urine 10), 161 bovine (102 sera, 49 urine, 3 milk and 7aborted contents), 153 rodent (60 sera, 33 urine and 60 kidney tissues), 177 swine sera and 166 human sera were collected with the unknown disease status. DFM revealed that canines (2.7 % sera and 40 % urine), bovines (4 % urine and 0.9 % sera), rodents (5 % sera and 9 % urine) and human (0.6% sera) samples were positive. PCR revealed that in canine (19.4 % sera and 60 % urine), bovine (5.8 % sera, 10.2% urine, 100% milk and 14.2% aborted contents), rodent (8.3% sera, 12.1 % urine and 13.3% kidney tissues), and human (0.6% sera) positivity for leptospirosis. Dark Field Microscopy can be used as a screening but when combine with Polymerase Chain Reaction can be utilized efficiently for detection of pathogenic leptospires.